Reimagining Qawaid Education: The Role of Cooperative Learning Strategies in Arabic Grammar Instruction - Syifa Pauzia Habsi Syifa; Rahmawati Rahmawati; Asrina Asrina; Yasmadi Yasmadi; Yufni Faisol (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
Qawaid (Arabic grammar) learning is often perceived as difficult and less engaging because it is commonly taught through conventional teacher-centered methods. This condition leads to low student participation, limited learning motivation, and difficulties in understanding and applying Arabic grammatical rules. Therefore, innovative instructional approaches are needed to create a more active, collaborative, and meaningful learning environment. This study aims to examine the effectiveness of cooperative learning strategies in improving students’ mastery of qawaid while fostering their social and collaborative skills. This study employed a quantitative approach using an experimental design involving Madrasah Aliyah students as research participants. Data were collected through observation, interviews, and documentation, and were analyzed by comparing learning conditions before and after the implementation of cooperative learning strategies. The findings reveal that cooperative learning significantly improves students’ understanding of qawaid, promotes active classroom participation, and enhances students’ motivation to learn. Furthermore, students demonstrated better collaboration and communication during the learning process. The study concludes that cooperative learning is an effective innovation in Arabic grammar instruction because it not only improves academic achievement but also develops students’ communication, teamwork, and responsibility skills. These findings contribute to the field of Arabic language education by providing practical insights for teachers seeking innovative and student-centered instructional strategies to enhance the quality of qawaid learning